Konjunkturprognosen: Verfahren, Erfolgskontrolle und Prognosefehler - Michael Grömling (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2005)
The economic forecasts for Germany in the period 2001 to 2003 grossly missed reality. Forecasters estimated an average annual growth rate of 1.6 per cent, but real GDP actually grew by only 0.3 per cent per annum. In 2003 the real GDP in Germany even shrank by 0.1 per cent. Forecasters tend to be generally optimistic. The analysis of the forecasts in the years 1995 to 2004 shows nevertheless that they were for the most years fairly accurate. In addition, the article gives several arguments which may explain forecast errors: data revisions, unpredictable events, behavioural and political feedback and imitation behaviour of forecasters.
Keywords: C52; C53; E37; E32; 330; Forecasting; Forecast evaluation; Forecast error; Business cycles; Germany; Konjunkturprognose; Prognoseverfahren; Statistischer Fehler; Schätzung; Deutschland